2011
DOI: 10.1002/bies.201100099
|View full text |Cite
|
Sign up to set email alerts
|

The evolution of menstruation: A new model for genetic assimilation

Abstract: Why do humans menstruate while most mammals do not? Here, we present our answer to this long-debated question, arguing that (i) menstruation occurs as a mechanistic consequence of hormone-induced differentiation of the endometrium (referred to as spontaneous decidualization, or SD); (ii) SD evolved because of maternal-fetal conflict; and (iii) SD evolved by genetic assimilation of the decidualization reaction, which is induced by the fetus in non-menstruating species. The idea that menstruation occurs as a con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
83
0
3

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 151 publications
(87 citation statements)
references
References 66 publications
1
83
0
3
Order By: Relevance
“…The decidua will be useful if there is a pregnancy, but otherwise it had to be shed by the monthly menstruation. 22 …”
Section: Concealment Of Ovulationmentioning
confidence: 99%
“…The decidua will be useful if there is a pregnancy, but otherwise it had to be shed by the monthly menstruation. 22 …”
Section: Concealment Of Ovulationmentioning
confidence: 99%
“…However, in humans and menstruating primates decidualization is initiated in response to ovarian hormones independently of an implanting blastocyst (2). Full differentiation and maintenance of the decidua is contingent upon pregnancy, since the absence of a conceptus provokes shedding of the pre-decidualized endometrial layer and menstruation, and it has been suggested that the evolution of spontaneous decidualization necessitated menstruation (3). This intriguing observation led us to propose that the gene regulatory pathways that coordinate spontaneous decidualization in menstruating primates are the key pathways dysregulated in endometriosis (4).…”
Section: Introductionmentioning
confidence: 99%
“…More accurately, they focused on ''spontaneous'' decidualization, a process that precedes the shedding of the endometrium in all known menstruating species (i.e. higher primates, some bats, and the elephant shrew) [1].…”
mentioning
confidence: 99%